New Report Calls for Coordinated Action to Tackle Employment Barriers Facing English Speakers in Capitale-Nationale - Provincial Employment Roundtable (PERT) (2024)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2024)

Socio-Demographic Characteristics of Visible Minorities in Québec City - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for Québec City, which is considered a territory equivalent to an MRC.

Socio-Demographic Characteristics of Visible Minorities in RTS de la Capitale-Nationale - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de la Capitale-Nationale.

RTS de la Capitale-Nationale - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Capitale-Nationale - Total Population, 2021 - Community Health and Social Services Network (CHSSN) (2024)

Employment Profile of English Speakers in Capitale-Nationale - Provincial Employment Roundtable (PERT) (2024)
This report aims to contribute to the knowledge and understanding of the employment situation of Capitale-Nationale’s English-speaking communities, who are linguistic minorities in the region. It surveys the most current and comprehensive information on their demographic and labour force conditions. Topics covered include work activity, unemployment rate, income, and educational attainment of workers to provide a more holistic picture of English speakers’ employment and employability. In addition to examining the demographics and labour force of the region’s English-speaking population, this profile also examines the key characteristics of the labour market and industries in which English speakers work. The profile concludes with identifying some of the employment challenges and issues English-speaking workers in Capitale-Nationale face, as well as preliminary recommendations to help improve their labour market outcomes.

Demographic Profiles of Québec's English-speaking Communities RTS de la Capitale-Nationale - Pocock, Joanne (Baseline Data Report Series, 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2022)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2022)

List of Employers in Quebec City Region with Jobs That Require English Skills - Voice of English-speaking Quebec (VEQ) (2022)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2022)

2021-2022 Annual Report : Saint Brigid's Home Residents' Committee - King, Kerry-Anne (Jeffery Hale - Saint Brigid's (JHSB), 2022)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2022)

Welcome to Kindergarten : Information for Parents / Bievenue à la maternelle : Information aux parents - Jeffery Hale - Saint Brigid's (JHSB) (2022)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2022)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2022)

Society Pages - Morrin Centre (2022)

Society Pages - Morrin Centre (2022)

Employment Profile of English Speakers in Capitale-Nationale - Provincial Employment Roundtable (PERT) (2022)
This profile aims to contribute to the knowledge and understanding of the employment issues faced by Capitale-Nationale’s English-speaking communities by surveying the most comprehensive information on the demographic and labour force conditions of English speakers in the region. The profile compiles the available data on English speakers’ employment status with respect to their position as linguistic minorities in majority French-speaking communities. For this reason, most of the information presented in this profile is organized by the two linguistic categories of English speakers and French speakers. In addition to examining the demographics and labour force of the English-speaking population, this profile also surveys Capitale-Nationale’s economic structure, as well as the work activity, income, and educational attainment of workers with the goal of providing a more holistic picture of employment and employability.

VEQ Newsletter December 2021 - Voice of English-speaking Quebec (VEQ) (2021)

VEQ Newsletter November 2021 - Voice of English-speaking Quebec (VEQ) (2021)

Evaluation of the Quebec Community Health and Social Service Foundation's (QCHF) Patient Navigator Project - Anastasopoulos, Vanessa (2021)

2020-2021 Annual Report: Saint Brigid’s Home Residents’ Committee - CHSLD Saint Brigid’s Home (SBH) (2021)

[Dashboards - Quebec and RTS Territories] - Community Health and Social Services Network (CHSSN) (2021)

RTS de la Capitale-Nationale - Population Aged 55 Years And Over, 2021 - Community Health and Social Services Network (CHSSN) (2021)

Report to the community : Highlights from 2019-2021 and overview of where we’re headed - Jeffery Hale - Saint Brigid's (JHSB) (2021)

Society Pages - Morrin Centre (2021)

Society Pages - Morrin Centre (2021)

Society Pages - Morrin Centre (2021)

Society Pages - Morrin Centre (2021)

VEQ Newsletter Spring 2021 - Voice of English-speaking Quebec (VEQ) (2021)

VEQ Newsletter Summer 2021 - Voice of English-speaking Quebec (VEQ) (2021)

The Holland Centre Experience : A Community Development Model for Minorities - Walling, Richard (Holland Resources Development Corporation, 2021)
The Holland Centre is a partnership of four public organisations and one private non-profit community organisation that has been successful in creating culturally-appropriate health and social services for a minority community in the province of Quebec, Canada. In June 1999 the J.W. McConnell Foundation awarded a grant to the Holland Centre that allowed it the time and resources necessary to analyse the elements of the centre’s success and develop the tools necessary to assist other linguistic minority communities to develop essential services.

VEQ’s Fall Winter 2020 Newsletter - Voice of English-speaking Quebec (VEQ) (2020)

Did You Know That English-Speaking Kindergarten Children Are More Vulnerable? - Community Health and Social Services Network (CHSSN) (2020)

VEQ’s Summer 2020 Newsletter - Voice of English-speaking Quebec (VEQ) (2020)

[Jeffery Hale Residents' Committee List / Jeffery Hale comité des résidents liste de membres] - Jeffery Hale - Saint Brigid's (JHSB) (2020)

Saint Brigid's Residents' Committee / Saint Brigid's comité des résidents - Jeffery Hale - Saint Brigid's (JHSB) (2020)

2019-2020 Annual Report : Saint Brigid's Home Residents' Committee - Leger, Valerie (Jeffery Hale - Saint Brigids (JHSB), 2020)
The roles and responsibilities of our Residents’ Committee (shared with the Users’ Committee) are to: 1. Inform users of their rights and obligations. 2. Help improve the quality of living conditions and evaluate the degree of satisfaction with the services at the institution. 3. Defend the collective rights and interests of users or, upon request, the rights and interests of an individual user, before the institution or any competent authority. The SBH Residents’ Committee is overseen by the JHSB Users’ Committee. As president, I therefore attended its meetings to receive and give information of interest to SBH. As committees we strive to work closely with administrators at SBH to ensure our concerns translate into quality services for residents.

39th Annual General Meeting - Voice of English-speaking Quebec (VEQ) (2020)

[Jeffery Hale - Saint Brigid’s Users’ Committee Annual Report : 2019-2020] - Jeffery Hale – Saint Brigid’s Users’ Committee (Jeffery Hale - Saint Brigids (JHSB), 2020)
The Jeffery Hale – Saint Brigid’s Users’ Committee met nine times from April 2019 to February 2020 in addition to its Annual Meeting on May 8, 2019. The Annual Meeting was held in conjunction with an Information Meeting by the Administration for Saint Brigid’s Residents and families and was well attended. The March 2020 meeting was cancelled because of the Covid19 virus pandemic. Throughout the year the Committee’s meetings were held in the Saint Brigid’s Boardroom because of renovations to the Jeffery Hale Pavilion.

Things to Do While You're at Home - Voice of English-speaking Quebec (VEQ) (2020)

Things to Do While You're at Home - Voice of English-speaking Quebec (VEQ) (2020)

Things to Do While You're at Home - Voice of English-speaking Quebec (VEQ) (2020)

Things to Do While You're at Home - Voice of English-speaking Quebec (VEQ) (2020)

Things to Do While You're at Home - Voice of English-speaking Quebec (VEQ) (2020)

Things to Do While You're at Home - Voice of English-speaking Quebec (VEQ) (2020)

Things to Do While You're at Home - Voice of English-speaking Quebec (VEQ) (2020)

Things to Do While You're at Home - Voice of English-speaking Quebec (VEQ) (2020)

Things to Do While You're at Home - Voice of English-speaking Quebec (VEQ) (2020)

VEQ’s Spring 2020 Newsletter - Voice of English-speaking Quebec (VEQ) (2020)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2020)

The Philanthropist : The Life and Legacy of Jeffery Hale - Donovan, Patrick (Jeffery Hale - Saint Brigids (JHSB), 2020)
In Quebec City, people associate the name Jeffery Hale with a hospital. While Hale certainly helped create the institution that bears his name, his story and legacy go well beyond its walls. Unlike most English-speaking immigrants who came to Canada, Jeffery Hale’s ancestors were rich, powerful, and very well connected. They lived a privileged life with strong transatlantic ties to the Royal Family and the colonial military. They furthered a British imperialist agenda and made decisions that shaped the destiny of North America.

Newsletter - Youth for Youth Québec (Y4Y Québec) (2020)

Adapting Services During the Pandemic : The Example of Jeffery Hale-Saint Brigid's and Its Partners - Duchesne, Anne (2020)

[Jeffery Hale - Saint Brigid's Friends' Foundation Annual report 2019-2020] - Jeffery Hale – Saint Brigid’s Friends’ Foundation (Jeffery Hale - Saint Brigid’s (JHSB), 2020)

Jeffery Hale-Saint Brigid's Friends' Foundation Annual Report 2019-2020 - Jeffery Hale – Saint Brigid’s Friends’ Foundation (Jeffery Hale - Saint Brigid's (JHSB), 2020)
The mission of the Friends' Foundation is to raise money to support Jeffery Hale - Saint Brigid's in its quest to provide quality health and social services to all its residents and clients. This report presents the results of the Friends’ Foundation’s projects financed for the year 2019.

Annual Report 2019-2020 : Learning in the Next Decade of Education - Leading English Education and Resource Network (LEARN) (2020)

Society Pages - Morrin Centre (2020)

Society Pages - Morrin Centre (2020)

Society Pages - Morrin Centre (2020)

Society Pages - Morrin Centre (2020)

Baseline Data Report 2019-2020 : Time Series Report : CHSSN-CROP Surveys 2005-2019 : Access to English-language Health and Social Services in Québec : RTS de la Capitale-Nationale - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2020)
The 2019-2020 Baseline Data Report (BDR) relays the health and social service findings of the CHSSN/CROP provincial survey of English speakers conducted in 2005, 2010, 2015 and 2019. This report is the first in the Baseline Data Report series to present the CHSSN/CROP provincial survey results from four different time periods. In keeping with the standard CHSSN reporting approach, survey results are organized according to the location of respondents in regional communities across Québec’s adminstrative territory and delineated into sub-groups defined by gender, age, household income, and knowledge of English and French. For report graphs, CHSSN selected two population groups considered vulnerable by many stakeholders with respect to access and language of service due to their age and level of bilingualism. It should be noted that in 2019, the CHSSN provincial survey questionnaire was significantly modified and the title of the survey changed to Community Health and Social Survey to reflect an increased focus on health sector issues. Importantly, despite these changes a sizable number of questions have remained identical and nearly identical across each rendition of the questionnaire. The responses to the questions that reoccurr from 2005 through to 2019 form the basis of these profiles. Information on health and social services access among English-speaking communities gathered through sampling techniques other than CROP telephone interviews are not included.

Report on Youth Employability in the Greater Quebec City Region - Voice of English-speaking Quebec (VEQ) (2020)
In the winter of 2019-2020, we conducted a survey of English-speaking youth aged 15 to 29 as well as six focus groups at the English high schools in the region to support two projects related to youth employability. Through our needs analysis, we sought to evaluate youth knowledge and/or use of the services offered by the Carrefour jeunesse-emploi centres as well as to gain some insights into the postsecondary education and career plans of the students at the local English high schools. These results are meant to provide a snapshot of the perspectives of Englishspeaking youth on employment in the Greater Quebec City region at this time. Though small in scope and sample size (53 survey participants, 32 focus group participants), this study captures the very real hopes and frustrations of our minority population. At the same time, it also proposes some very concrete and achievable outcomes. We hope that this document can serve as a springboard for employers and service providers to work with us, and members of our community, to increase the employability of English-speaking youth in the Greater Quebec City region. Let’s build a better future for all Québécois.

Services d'éducation spécialisé pour parents d'enfants de 0 à 16 ans - Jeffery Hale - Saint Brigid's (JHSB) (2019)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2019)

VEQ’s Summer 2019 Newsletter - Voice of English-speaking Quebec (VEQ) (2019)

Practice Makes Perfect - Voice of English-speaking Quebec (VEQ) (2019)

2018-2019 Annual Report - Voice of English-speaking Quebec (VEQ) (2019)

Breastfeeding Get Together - Jeffery Hale Community Services (2019)

Financial Statements - Voice of English-speaking Quebec (VEQ) (2019)

VEQ’s Spring 2019 Newsletter - Voice of English-speaking Quebec (VEQ) (2019)

Community Health Education Program (CHEP) 2018-2019 - Community Health and Social Services Network (CHSSN) (2019)
The CHSSN Community Health Education Program (CHEP) serves the urban, rural and remote English-speaking communities around the province of Quebec, providing health and social information and support via video conferencing through the RUIS (McGill) Telehealth system. Twenty community NPI networks funded under the CHSSN Network Partner Initiative (NPI) from across the province of Quebec participated, by attending the CHEP video conferences and by hosting a CHEP DVD viewing session. The following report highlights the Community Health Education Program (CHEP) activities for the period from April 1, 2018, to March 31, 2019.

Community NetLink - Community Health and Social Services Network (CHSSN) (2019)

Vitality - Community Health and Social Services Network (CHSSN) (2019)
Keywords: Official Language Minority Community (OLMC)

Who We Are - Community Health and Social Services Network (CHSSN) (2019)

Report to the Community : Highlights from 2018-2019 and Overview of Where We're Headed - Jeffery Hale - Saint Brigid's (JHSB) (2019)

Annual Report 2018-2019 - Leading English Education and Resource Network (LEARN) (2019)

Society Pages - Morrin Centre (2019)

Society Pages - Morrin Centre (2019)

Society Pages - Morrin Centre (2019)

Society Pages - Morrin Centre (2019)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2018)

VEQ's Summer 2018 Newsletter - Voice of English-speaking Quebec (VEQ) (2018)

Demographic Profile of the English-speaking Communities in the Administrative Region of Capitale-Nationale & MRC La Côte-de-Beaupré - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Capitale-Nationale & MRC La Jacques-Cartier - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Capitale-Nationale & MRC Portneuf - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Capitale-Nationale & MRC Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

VEQ's Spring 2018 Newsletter - Voice of English-speaking Quebec (VEQ) (2018)

Chit Chat Club : Improve Your Second Language Skills While Lending a Helping Hand - Centre Wellness (2018)

Adaptation Initiative Project Guide 2014-2018 - Community Health and Social Services Network (CHSSN) (2018)
The CHSSN’s initiative to adapt health and social services is supported by an investment from Health Canada, through the Roadmap for Canada's Official Languages 2013–2018: Education, Immigration, Communities. This initiative is being undertaken in partnership with the Ministère de la Santé et des Services sociaux (MSSS). An implementation agreement between CHSSN and the MSSS was concluded in order to incorporate the projects into Quebec’s initiatives to improve access to health and social services in English. The agreement also divided the roles and responsibilities among the CHSSN, the MSSS, and the health and social services agencies.

Adaptation Initiative Project Guide 2018-2023 - Community Health and Social Services Network (CHSSN) (2018)
Keywords: Official Language Minority Community (OLMC)

Québec Health 101 Guide - Jeffery Hale Community Services; Community Wellness Centre; Voice of English-speaking Quebec (VEQ) (2018)
This guide and the accompanying presentation were developed with the intention of helping newcomers navigate the medical system here in Québec City with a little more ease and efficiency. This project was a joint effort between Jeffery Hale Community Services, the Community Wellness Centre and the Voice of English-speaking Québec. This document was inspired by the Valcartier Family Centre Health Guide.

Annual Report 2017-2018 : Leading the Way - Leading English Education and Resource Network (LEARN) (2018)

Society Pages - Morrin Centre (2018)

Society Pages - Morrin Centre (2018)

Society Pages - Morrin Centre (2018)

Society Pages - Morrin Centre (2018)

Annual Report 2017-2018 - Voice of English-speaking Quebec (VEQ) (2018)

Travellin' Toddler Time : 2018-2019 Schedule - Voice of English-speaking Quebec (VEQ) (2018)

Improving the Spectrum of Services Offered to English-Speaking Seniors : CIUSSS de la Capitale-Nationale’s Experience Implementation Project: 2014-2018 - Paquette, Brigitte (2017)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2017)

A Website Created to Support English-speaking Patients from Eastern Regions in Quebec Traveling Away from Home for Medical Services - Community Health and Social Services Network (CHSSN) (2017)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2017)

Policy for Use of the Dynamic Signage System / Politique d'utilisation du système d'écrans dynamiques - Jeffery Hale - Saint Brigid's (JHSB) (2017)

Employment in the Québec Regions : Needs Assessment Study - Youth Employment Services (YES) (2017)
The current needs assessment was developed with the vision of understanding the socioeconomic conditions of seven Quebec regions examined by this study, namely, Gaspésie-Îles-de-la-Madeleine, Capitale-Nationale, Chaudière-Appalaches, Estrie, Montérégie, Côte-Nord and Abitibi-Témiscamingue. The study also involved conducting an inventory of job search and employment-related services in these seven Québec regions, and identifying the needs of English-speaking job seekers residing in the regions. The intent of this study is to inform the development of timely, evidence-based English-language employment services and career supports in the regions, ultimately leading to increased economic opportunities and stability for English-speaking youth (aged 16-35) in Québec. A related goal is to increase awareness of English-language employment services and supports available to job seekers in the Québec regions.

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2017)

Welcome to Saint Brigid’s Home Residential and Long Term Care Center : Welcome Guide for Residents and their Loved Ones - Jeffery Hale - Saint Brigid's (JHSB) (2017)

Access to Public Long-term Care : Useful information for seniors and their loved ones - Jeffery Hale Community Services (2017)

Saint Brigid's Residents' Committee : Welcome to Your Home! / Saint Brigid's Comité des résidents : Bienvenu(e) chez vous ! - Jeffery Hale - Saint Brigid's (JHSB) (2017)

Building Together : Succesful Partnerships Between Community and the Health and Social Services System - Community Health and Social Services Network (CHSSN) (2017)
The Community Health and Social Services Network (CHSSN) coordinates a Quebec-wide health and social services “Adaptation Program” designed to enhance the vitality of English-speaking minority communities in Quebec by increasing access to existing health and social services for Englishspeaking Quebecers. The program is supported by an investment from Health Canada and has been undertaken in partnership with the ministère de la Santé et des Services sociaux (MSSS). An implementation agreement between CHSSN and the MSSS was concluded to incorporate the projects into Quebec’s initiatives to improve access to health and social services in English through partnerships between local English-speaking communities and health and social services system.
Keywords: Official Language Minority Community (OLMC)

Annual Report 2016-2017 - Leading English Education and Resource Network (LEARN) (2017)

Society Pages - Morrin Centre (2017)

Society Pages - Morrin Centre (2017)

Society Pages - Morrin Centre (2017)

Society Pages - Morrin Centre (2017)

Demographic Profiles of English-speaking Communities : RTS de la Capitale-Nationale - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Capitale-Nationale & RLS de Portneuf (0311) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Capitale-Nationale & RLS de Québec-Sud (0312) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Capitale-Nationale & RLS Québec-Nord (0313) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Annual Report 2016-2017 - Voice of English-speaking Quebec (VEQ) (2017)

CLC Chronicles 2015-2016 - Leading English Education and Resource Network (LEARN) (2016)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2016)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2016)

Update - Leading English Education and Resource Network (LEARN) (2016)

Year-End Report - Leading English Education and Resource Network (LEARN) (2016)
The Leading English Education and Resource Network (LEARN) is a non-profit organization that serves the public, private, anglophone and aboriginal Youth and Adult Education sectors of Québec. We bring together the expertise and efforts of educators, students, parents and partners in our community to cultivate success for all learners.

ELAN Presents Arts Alive! Québec - English Language Arts Network (ELAN) (2016)

In Touch - Jeffery Hale - Saint Brigid's (JHSB) (2016)

Your Child's Health : Children and Sleep - Jeffery Hale - Saint Brigid's (JHSB) (2016)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2016)

Children 0 to 5 and their Parents : RTS de la Capitale-Nationale - Community Health and Social Services Network (CHSSN) (2016)

Provincial Resource Team Report 2015-2016 - Leading English Education and Resource Network (LEARN) (2016)
Over the last ten years, English schools in Quebec have increasingly embraced the dual role of supporting student perseverance and contributing to the vitality of their English-speaking communities. With more than 80 schools and adult education centres across the province now part of the Community Learning Centre (CLC) network, it is evident that School Boards are adopting a new way of thinking about school and community partnerships. This “integrated focus on academics, services, supports and opportunities leads to improved student learning, stronger families and healthier communities. Schools become centers of the community”
Keywords: Official Language Minority Community (OLMC)

Society Pages - Morrin Centre (2016)

Society Pages - Morrin Centre (2016)

Society Pages - Morrin Centre (2016)

Society Pages - Morrin Centre (2016)

Gender Based Socio-demographic Profiles : Volume 1 : English-speaking Men and Fathers : RTS de la Capitale-Nationale - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 1 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the men and fathers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. Volume 2 presents the same information for English-speaking women and mothers. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS de la Capitale-Nationale - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Regional Mini Portraits - Pocock, Joanne (2016)
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS de la Capitale-Nationale - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS de la Capitale-Nationale - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Annual Report 2015-2016 - Voice of English-speaking Quebec (VEQ) (2016)

Community Consultation 2015-2016 - Voice of English-speaking Quebec (VEQ) (2016)

Partner Survey 2015-2016 - Voice of English-speaking Quebec (VEQ) (2016)

The English-speaking Community of the Greater Quebec Region - Voice of English-speaking Quebec (VEQ) (2016)

Inter-regional Access to Specialized Health and Social Services for English-speakers from Eastern Quebec - Richardson, Mary (2015)
Keywords: Official Language Minority Community (OLMC)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2015)

[Complaint or Positive Comment Form / Formulaire de plainte ou commentaire positif] - Jeffery Hale - Saint Brigid's (JHSB) (2015)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2015)

A Road Map to your Caregiving Journey : A Practical Handbook for English-speaking Caregivers in the Great Quebec City Region - Jeffery Hale Community Partners (2015)

Action prévention : La sécurité est notre responsabilité à tous - Haberlin, John (2015)

The Policy on Language of Service - Jeffery Hale - Saint Brigid's (JHSB) (2015)
The objective of this policy is to ensure that employees communicate effectively with both French and English‐speaking clients and that Language Assistance Services are also available for other Limited‐French or English Proficient (LFEP) individuals and their surrogate decision‐makers at all points of contact, in a timely fashion and in their preferred language in order to ensure an understanding of their health condition and treatment options.

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2015)

Community Vitality Survey of the English-speaking Community of Quebec - Community Health and Social Services Network (CHSSN) (2015)

Partnering for the Well-being of Minority English-Language Youth, Schools & Communities - Gonsalves, Allison; Kueber, Russell; Langevin, Paule; Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2015)
This document identifies some of the unique challenges, strengths, and aspirations of English-speaking youth in Quebec and provides a school and community-based framework for action intended to have a positive impact on their well-being and educational success. It emerges from the collaboration of community health and social services networks, called (NPIs) - abbreviation for the Networking and Partnership Initiative and Community Learning Centers (CLCs) seeking to improve the overall well-being of minority language youth residing in province.
Keywords: Official Language Minority Community (OLMC)

CLC Initiative Annual Report of Activities - Leading English Education and Resource Network (LEARN) (2015)
Keywords: Official Language Minority Community (OLMC)

Society Pages - Morrin Centre (2015)

Society Pages - Morrin Centre (2015)

Society Pages - Morrin Centre (2015)

Society Pages - Morrin Centre (2015)

Annual Report 2014-2015 - Voice of English-speaking Quebec (VEQ) (2015)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2014)

2013-2014 Annual Report of CLC Activities - Leading English Education and Resource Network (LEARN) (2014)
Keywords: Official Language Minority Community (OLMC)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2014)

June 12, 2014 - Leading English Education and Resource Network (LEARN) (2014)

Recovery Support Program : A Community Wellness Program for English-speaking People with Mental Illness - Jeffery Hale - Saint Brigid's (JHSB) (2014)

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Beauport (03032) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Charlesbourg (03034) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Duberger Les Saules Lebourgneuf (03026) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Limoilou-Vanier (03025) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Loretteville Val Belair (03031) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Orleans (03033) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Quebec-Basse-Ville (03024) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Quebec-haute-ville (03023) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Sainte-foy-Sillery (03022) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS de Portneuf (0301) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS Quebec-nord (0303) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS Vieille-capitale (0302) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2014)

Literary and Historical Society of Quebec - Morrin Centre (2014)

Society Pages - Morrin Centre (2014)

Society Pages - Morrin Centre (2014)

Society Pages - Morrin Centre (2014)

Annual Report 2013-2014 - Voice of English-speaking Quebec (VEQ) (2014)

Disclosure : Your Right to be Informed / Divulgation : Le droit d'être informé - Jeffery Hale - Saint Brigid's (JHSB) (2013)

Jeffery Hale - Saint Brigid's at a Glance - Jeffery Hale - Saint Brigid's (JHSB) (2013)

Strategic Plan 2012 - 2015 : Summary Document - Jeffery Hale - Saint Brigid's (JHSB) (2013)

Community Learning Centres : Changing Lives and Communities Annual Report of Activities - Leading English Education and Resource Network (LEARN) (2013)
This year the 37 Community Learning Centres across Quebec worked collaboratively with more than 700 local, regional, provincial, and national partners, to leverage in excess of $3 million of in-kind services and resources to serve their schools and communities. CLCs are doing more than just leveraging resources; they are changing lives and communities. They serve as a place for education and community development, and have become an important part of collaborative community change efforts. The stories and best practices highlighted in this annual report capture the essence of the initiatives being implemented by CLCs to achieve change and progress in English speaking communities across Quebec. Highlights of the activities undertaken in 2012-2013 begin with how one of our most important stakeholder groups, our teachers, are engaging with our initiative. The Community-Based Learning approach is just one example of the many strategies CLCs are adopting to impact students and develop a culture of lifelong learning. This year’s activities also included many examples of in-school and after-school activities in which CLC students are learning about incorporating healthy living options into their lives as well learning about aboriginal culture and building relationships between aboriginal and non-aboriginal communities. CLCs mobilize community and partner support to address current and important needs in our schools, including improving school climate and reducing bullying. Their activities for adults and seniors demonstrate to students that learning truly is a lifelong process. Engaging parents before their children have even entered school and continuing to find ways to connect and support parents throughout school life is an ongoing and important part of our work.

June 13, 2013 - Leading English Education and Resource Network (LEARN) (2013)

Report : Future Forum of the English-speaking Community - Future Forum of the English-speaking Community (Voice of English-speaking Quebec (VEQ), 2013)
The Future Forum was held on November 24th, 2012 from 9 am - 2 pm at Eastern Québec Learning Center in Quebec City, Québec. The purpose of the event was to share opinions on the current state, needs and challenges of the English-speaking community while generating a shared vision for our future.

Preventing Pressure Sores : A Guide for Clients and Their Families / Prévention des plaies de pression : Un guide à l'intention des patients et de leurs familles - Jeffery Hale - Saint Brigid's (JHSB) (2013)

Fall Prevention : Information for Clients and Their Families - Jeffery Hale - Saint Brigid's (JHSB) (2013)

Restraints : Information for Clients and Families / Mesures de contrôle : Publications aux usagers et aux proches - Jeffery Hale - Saint Brigid's (JHSB) (2013)

Infection Control : Important Facts for Families, Volunteers and Visitors - Jeffery Hale - Saint Brigid's (JHSB) (2013)

Influenza : You Can Help Prevent and Control the Flu / Influenza : Vous pouvez aider à prévenir et contrôler la grippe - Jeffery Hale - Saint Brigid's (JHSB) (2013)

Roles and Responsibilities in Patient Safety : Physicians, Staff and Volunteers / Rôle et responsabilités dans la securité des patients : Médecins, personnel et bénévoles - Jeffery Hale - Saint Brigid's (JHSB) (2013)

Brief Regarding the General Consultation and Public Hearings on Bill 14 : An Act to Amend the Charter of the French Language, the Charter of Human Rights and Freedoms and Other Legislative Provisions - Voice of English-speaking Quebec (VEQ) (2013)
The purpose of this brief is to highlight the potential impacts that the proposed Bill 14 could have on the minority English-speaking community of the Greater Quebec City region. As the preeminent interest group representing English-speakers in the Quebec City region, VEQ has carefully analyzed all the modifications included in the proposed Bill 14 and has consulted its membership, community and many of its key partners in order to present this comprehensive evaluation of the impacts that Bill 14 could have on our community. It is our opinion that Bill 14, if adopted in its present form, will have several negative consequences on the vitality of our community and on the capacity of English speakers to continue to be contributing citizens of our region. In addition, we sincerely believe that Bill 14 will also have a real negative impact on the capacity of our entire region to attract and retain English-speaking immigrants and migrants which will directly affect the economic prosperity of the Quebec City region.
Keywords: Official Language Minority Community (OLMC)

Society Pages - Morrin Centre (2013)

Society Pages - Morrin Centre (2013)

Society Pages - Morrin Centre (2013)

Society Pages - Morrin Centre (2013)

Annual Report 2012-2013 - Voice of English-speaking Quebec (VEQ) (2013)

Update - Leading English Education and Resource Network (LEARN) (2012)

Saint Brigid's and its Foundation : A Tradition of Caring Since 1856 - Donovan, Patrick (Jeffery Hale - Saint Brigids (JHSB), 2012)
Excursions have always been part of Saint Brigid’s history. In the summer of 1894, the orphans piled into horse-drawn trams and wagons headed for the rural hinterland of Sainte Foy, where they enjoyed a picnic on Mr. Boyce’s farm. While horse-drawn trams are a thing of the past, and Sainte Foy now has more parking lots than farms, the home’s residents still enjoy trips to see the fall colours, go fishing, or enjoy a spot of shopping. In the following pages, the SAINT BRIGID’S HOME FOUNDATION invites you on a different sort of journey: a trip through time that takes you from the beginnings of the home to the present day.

Society Pages - Morrin Centre (2012)

Society Pages - Morrin Centre (2012)

Society Pages - Morrin Centre (2012)

Society Pages - Morrin Centre (2012)

Annual Report 2011-2012 - Voice of English-speaking Quebec (VEQ) (2012)

Specialized Geriatric and Psychogeriatric Consultation Team - Jeffery Hale - Saint Brigid's (JHSB) (2011)

Public Health Action Plan for the English-Speaking Community in the Capitale-Nationale Region 2011-2015 - Jeffery Hale - Saint Brigid's (JHSB) (2011)
Saint Brigid’s – Jeffery Hale Hospital’s Public Health Action Plan for the English- Speaking Community in the Capitale-Nationale Region is in keeping with the Plan d’action regional (PAR) en santé publique 2009-2012 (regional public health action plan) developed by the Agence de la santé et des services sociaux de la Capitale-Nationale (Agence). To ensure viable results for our efforts aimed at improving the health and well-being of the English-speaking community, we thought it relevant to begin by presenting an updated portrait of the English-speaking community in the CNR. This portrait allows us to identify the various needs of the community, as well as its health determinants and indicators, and take stock of its ongoing evolution. This description is followed by a detailed presentation of Saint Brigid’s – Jeffery Hale Hospital’s prevention and health promotion Service Offer.

Society Pages - Morrin Centre (2011)

Society Pages - Morrin Centre (2011)

Society Pages - Morrin Centre (2011)

Annual Report 2010-2011 - Voice of English-speaking Quebec (VEQ) (2011)

Membership Socio-demographic Attributes 2010-11 - Voice of English-speaking Quebec (VEQ) (2011)

Service Offer : Jeffery Hale Community Services - Jeffery Hale - Saint Brigid's (JHSB) (2010)
Jeffery Hale Community Services (JHCS) has a delegated responsibility to offer primary, CLSC type services to the English-speaking population in the CNR, as well as support a coordinated, consolidated service offer for this community. Through alliances with community partners, we work on ensuring the development and vitality of the English-speaking community. JHCS provide youth and family services, mental health programs, and for seniors, home care and a day centre.

Presentation to the Standing Senate Committee on Official Languages - Gignac, Jean-Sébastien (2010)

Baseline Data Report 2009-2010 : Demographic Profiles of Quebec's English-speaking Communities by selected CSSS Territories - Pocock, Joanne; Warnke, Jan (Community Health and Social Services Network (CHSSN), 2010)
This document presents selected demographic characteristics of the English-speaking population of the CSSS territories in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI) of the Community Health and Social Services Network (CHSSN). The information presented is drawn from the 2006 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec's official language minoritty community.
Keywords: Official Language Minority Community (OLMC)

2009-10 Annual Report - Leading English Education and Resource Network (LEARN) (2010)
In a province as vast as Quebec, and with schools and school boards scattered over an enormous geographic expanse, the notion of bringing people together to create a COMMUNITY of collaboration may appear daunting, if not impossible. In reality, when people share similar interests and common goals, those physical impediments can quickly disappear. This is especially true when the ultimate objective is the academic success of our children in elementary and high schools. LEARN’s focus is to serve as a catalyst and facilitator for the creation of communities of collaboration composed of educators, parents and students across the province. It is our organization’s objective to make every effort possible to get the well-intentioned forces within the English educational milieu together to share the wealth of knowledge and experience that resides there.

Society Pages - Morrin Centre (2010)

Society Pages - Morrin Centre (2010)

Society Pages - Morrin Centre (2010)

Society Pages - Morrin Centre (2010)

Annual Report 2009-2010 - Voice of English-speaking Quebec (VEQ) (2010)

Ladies' Protestant Home 1859-2009 : 150 Years of History - Donovan, Patrick; Hayes, Ashli (2009)
This is the story of how, for the past 150 years, English-speakers in Quebec saw needs in the community and reached out to meet them. The Ladies’ Protestant Home was founded in 1859, a time when epidemics, poor work conditions, and frequent urban fires made life difficult for the poor. There was a crying need for institutions to help out. In its early years, the Home provided temporary shelter for poor and destitute Protestant immigrant women. Its mandate evolved over the years, with an increasing focus on serving the elderly from the 1950’s onward. The Home eventually reached out to non-Protestants, Francophones, and men before closing down in 1990. For the past two decades, the Quebec Ladies’ Home Foundation has continued to manage assets from the Home's sale towards the purpose of providing health and social services to English-speakers in Quebec City.

Society Pages - Morrin Centre (2009)

Society Pages - Morrin Centre (2009)

Society Pages - Morrin Centre (2009)

Annual Report 2008-2009 - Voice of English-speaking Quebec (VEQ) (2009)

A Study of Recruitment and Retention Factors Affecting Immigrants, and Anglophone Newcomers in the Quebec City Region - Voice of English-speaking Quebec (VEQ); Conférence régionale des élus de la Capitale-Nationale (2009)
This study focuses on the trends and community-based responses to in-migration in the Quebec City region. It is specifically concerned with issues pertaining to the local English-speaking community, a group that is vested with the legal and political designation of official language minority community by the federal government of Canada. The issue of in-migration is multifaceted and multidisciplinary. To wade into debates on the patterns and effects of migration over a given territory requires a significant amount of background knowledge from a number of different sources. Moreover, to consider the proper policy responses to migratory patterns, we must pay attention to wider political, sociological, and economic conditions that shape how individuals make decisions, such as why they move to a particular region, how long to stay and when to leave.

Delivering Health and Social Services in English to English-speakers in the Capitale-Nationale Region (CNR) Revised Access Program: 2006-2009 : Translated and Edited Version - Jeffery Hale - Saint Brigid's (JHSB) (2008)
To comply with the latter, the Capitale-Nationale Region's Health and Social Services Network Development Agency (CNR Agency) launched a review of the health and social services offered in English to English speakers in the region.

Questions and Answers about Access to Health and Social Services in English in the Capitale-Nationale Region (CNR) - Jeffery Hale - Saint Brigid's (JHSB) (2008)

Ancestors : Life, Death, and Descendants of Quebec City's Anglophones - Morrin Centre (2008)
Quebec City’s cemeteries have lots to say about our ancestors and the past. They are places of remembrance for those close to the departed, but they are also a storehouse of memories for the whole community. Cemeteries are closely linked to religious belief : They express a particular vision of the world, a set of values and a culture.

Building the City : The Influence of English Speakers on Quebec City's Architecture - Morrin Centre (2008)
Quebec City is praised for its quintessential Frenchness, yet a closer look at its architecture reveals a city with a strong British influence. Ninety-five per cent of the city was built or modified after the British conquest in 1759. In the middle of the ninete nth century, half the people in the Upper Town were English speakers, and they left a clear mark on the built environment. Many of the city’s important landmarks, from the Château Frontenac to the Price Building, were designed by English-speaking architects.

People and Faith : The Religious Life of English Speakers in Quebec City - Morrin Centre (2008)
Through this tour, you’ll learn about Quebec City’s anglophones through their places of religious worship and practice. We’ll look at distinctions between different forms of belief and you’ll gain a better understanding of Quebec’s religious landscape.

People of the River : Anglophone Life on the St. Lawrence - Morrin Centre (2008)
The Greek historian Herodotus summed up Egypt’s dependence on its great river by calling the country a “gift of the Nile.” In the same way, it could be said that Quebec is a gift of the St. Lawrence. The St. Lawrence was the “boulevard” of the territory’s first inhabitants, the Aboriginal people. Then it became the access route for French explorers. Samuel de Champlain thought it was a route to China, and this was a determining factor in his decision to found a colony at Quebec.

Rediscover Quebec City's Anglo Heritage Through Four Self-Guided Tours / Redécouvrez le visage anglophone de Québec à l'aide de quatre visites autoguidées - Morrin Centre (2008)

Society Pages - Morrin Centre (2008)

Society Pages - Morrin Centre (2008)

Society Pages - Morrin Centre (2008)

Society Pages - Morrin Centre (2008)

Annual Report 2007-2008 - Voice of English-speaking Quebec (VEQ) (2008)

Quebec City's Literary Heritage : A Bibliography - Donovan, Patrick (Literary & Historical Society of Quebebc, 2007)
The Literary and Historical Society of Quebec (LHSQ), founded in 1824, has a mandate to foster English-language culture in the Quebec City region and to share its diverse heritage. Literature is a vital element in this heritage, and the LHSQ has taken on a project to celebrate Quebec City’s English-language literary heritage. The first step of this project is to generate an accessible knowledge base, or bibliography. This tool will have several repercussions: book purchases for the LHSQ’s library, written articles to promote these books, and the hosting of literary events in 2007 and 2008. This project is financed by the Department of Canadian Heritage as part of the Development of Official-Language Communities Program - Community Life component.

Society Pages - Morrin Centre (2007)

Society Pages - Morrin Centre (2007)

Society Pages - Morrin Centre (2007)

Society Pages - Morrin Centre (2007)

Annual Report 2006-2007 - Voice of English-speaking Quebec (VEQ) (2007)

Society Pages - Morrin Centre (2006)

Society Pages - Morrin Centre (2006)

Society Pages - Morrin Centre (2006)

Society Pages - Morrin Centre (2006)

Society Pages - Morrin Centre (2005)

Society Pages - Morrin Centre (2005)

Society Pages - Morrin Centre (2005)

Society Pages - Morrin Centre (2005)

Listening to Our Young People : The VEQ Youth Report 2005 - Pitre, Edgard; Tomlinson, Patrick; Twardawa, Christopher (Voice of English-speaking Quebec (VEQ), 2005)
The following represents the findings of a youth study conducted by the Voice of English-speaking Québec (VEQ) in 2004 - Listening to Our Young People. The purpose of the study was to collect and correlate survey responses completed by Secondary IV and V, adult learning centre, and CEGEP 1, 2 and 3 Anglophones in the Greater Quebec City and Chaudières-Appalaches regions. The survey questions varied in scope but the general focus was concerned with the various aspects of daily life in and around Quebec City. By analyzing survey responses, VEQ hoped to arrive at a better understanding of the perceptions, positive and otherwise, young Anglophones have regarding their community.

Society Pages - Morrin Centre (2004)

Society Pages - Morrin Centre (2004)

Society Pages - Morrin Centre (2004)

Society Pages - Morrin Centre (2004)

Society Pages - Morrin Centre (2002)

Society Pages - Morrin Centre (2002)

Centre Hospitalier Jeffery Hale's Hospital Centre 1865-1990 - Gelly, Alain (1990)

City Trek '90 - O'Gallagher, Marianna (1990)

Brief to the Minister of Education Regarding the Cumulative School Record Presented by Quebec Federation of Home & School Associations - Quebec Federation of Home and School Associations (QFHSA) (1974)
The Quebec Federation of Home & School Associations, representing over 12,000 families who are members of local associations in schools or groups of schools, in preparing this Brief has received comments and assistance from associations on the Island of Montreal, the south and north shore , Quebec City, Hull, Gaspe and the Eastern Townships and also from a number of school committees .

81st Annual Report of Jeffery Hale's Hospital and the Training School for Nurses : with a List of the Governors, Officers, and Subscribers for 1946 - Jeffery Hale's Hospital (Jeffery Hale - Saint Brigids (JHSB), 1946)

Toddler Talk : For English-Speaking Families with Children Aged Four and Under - Centre Wellness

Citadel Foundation - Donovan, Patrick

Health and Social Services for Students in CQSB Schools in the Quebec City Region - Jeffery Hale - Saint Brigid's (JHSB)

Multimedia Theatre Presentation : The Philanthropist - Jeffery Hale - Saint Brigid's (JHSB)

Users and Residents : Have Your Say / Usagers et résidents : La parole est à vous - Jeffery Hale – Saint Brigid’s (JHSB) Users' Committee

Comité de résidents Saint Brigid’s Residents’ Committee : Bienvenue chez vous ! Welcome to Your Home! - Jeffrey Hale - Saint Brigid's (JHSB)

Morning Routines : Are You Ready for School? - Kulasingam, Mathuri

Together We Can Help Create an Ideal Learning Environment for All - Leading English Education and Resource Network (LEARN)

Memory Garden Project / Projet Jardin Souvenir - Saint Brigid’s Home

Get Involved, Connected & Meet New People! - Voice of English-speaking Quebec (VEQ)

The Many Faces of Elder Abuse - Voice of English-speaking Quebec (VEQ)
Voice of English-speaking Québec is proud to support English-speaking seniors in the greater Quebec City region. This booklet was produced to help seniors in our community stay independent, safe and to help prevent abuse and discrimination targeting them. This project is funded in part by Service Canada under the New Horizons for Seniors Program.